Impact of a critical thinking development program on Peruvian university students - Padilla Sánchez, Maribel Maribel (2024)
Critical thinking is a fundamental competency for university students, as it involves analyzing and judging even one’s own beliefs, which requires a willingness to change. This study aimed to determine whether it is possible to develop critical thinking through the PECRIT program in early childhood and primary education university students from a university in Huancayo. The research, with a quantitative approach, used a quasi-experimental design with two non-equivalent groups. The reactive indirect observation technique was employed, and a pedagogical test was applied as the instrument to measure the level of critical thinking. The population included 1,668 students from the Faculty of Education, from which a non-probabilistic sample of 129 students was selected: 60 comprised the experimental group and 69 the control group. The results showed significant improvements in the experimental group. At the primary level, performance increased from 67.85% in the pre-test to 96.4% in the post-test. Similarly, at the early childhood level, students improved from 34.37% to 93.75%. These findings highlight the effectiveness of the PECRIT program in developing critical thinking, outperforming the control group in areas such as perception, thinking, and willingness to change. It is concluded that the PECRIT program is highly effective in fostering critical thinking in university students, contributing to the formation of reflective individuals prepared to face current challenges.